2018
DOI: 10.1253/circj.cj-17-0510
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes Survey of Bone Marrow-Derived Cell Therapy in Critical Limb Ischemia in Japan

Abstract: Background:The Therapeutic Angiogenesis by Cell Transplantation (TACT) trial demonstrated the efficacy and safety of autologous bone marrow-derived mononuclear cells (BM-MNCs) in patients with critical limb ischemia (CLI). The present study aimed to assess the long-term clinical outcomes of therapeutic angiogenesis using autologous BM-MNC implantation under advanced medical treatment in Japan. Methods and Results:The study was retrospective, observational, and non-controlled. We assessed no-option CLI patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
(20 reference statements)
2
38
1
1
Order By: Relevance
“…The results confirmed that autologous BM-MNC treatment is clinically feasible and safe, especially in the case of TAO or CDV [22]. In China, a 10-year study on autologous BM-MNC treatment in CLI patients with thromboangiitis obliterans has shown that BM-MNC treatment is safe and effective.…”
supporting
confidence: 63%
“…The results confirmed that autologous BM-MNC treatment is clinically feasible and safe, especially in the case of TAO or CDV [22]. In China, a 10-year study on autologous BM-MNC treatment in CLI patients with thromboangiitis obliterans has shown that BM-MNC treatment is safe and effective.…”
supporting
confidence: 63%
“…11 Therapeutic angiogenesis by means of gene therapy and cell therapy, including autologous BM-MNC transplantation, peripheral mononuclear cell transplantation, and endothelial progenitor cell transplantation, is being developed to provide options for effective revascularization. [12][13][14][15][16] Cell therapy for CLI patients was first reported in Japan in 2002 by Tateishi-Yuyama et al, who investigated the…”
Section: Methodsmentioning
confidence: 99%
“…11 In previous clinical studies, the trend for major amputation in patients with CLI after bone marrow mononuclear cell (BM-MNC) implantation decreased in patients with atherosclerotic PAD and patients with TAO. [12][13][14][15][16] Patients with TAO have less remarkable underlying medical complications. Hence, limb salvage and survival rates are significantly higher in patients with TAO after cell therapy.…”
Section: Study Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, attempts have been made within Asia to investigate the use of other cells, such as adipose tissue-derived mesenchymal stem cells and peripheral blood mononuclear cells, for therapeutic angiogenesis in patients with TAO in addition to BM-MNCs, which have shown a certain degree of effectiveness (see Table). [4][5][6][7][8][9][10][11][12] Despite promising results from clinical trials, there are still many questions surrounding therapeutic angiogenesis, such as which stem cell types are most effective or efficient and whether hybrid treatment is desirable. Through further clinical studies, we hope that therapeutic angiogenesis through less invasive and more reliable cell transplantation…”
Section: Conflicts Of Interestmentioning
confidence: 99%